The influence of blood removal on pacing during a 4-minute cycling time trial - Lawler, N. G.; Abbiss, C. R.; Raman, A.; Fairchild, T. J.; Maker, G. L.; Trengove, R. D.; Peiffer, J. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: